Choosing the right packing in millipacked bed reactors under single phase gas flow. (15th February 2021) - Petrazzuoli, Vittorio; Rolland, Matthieu; Mekki-Berrada, Adrien; Said-Aizpuru, Olivier; Schuurman, Yves
Graphical abstract: Highlights: Focus on packed beds with diameter <1 cm packed with millimetric catalyst. Study of hydrodynamics and mass transfer with spherical beads and extrudates. Criterion for dispersion effects negligibility in millipacked bed reactors. Positive effect of the porosity fillers that are recommended in all cases. Spherical porosity fillers recommended as they yield lower void fraction. Abstract: Packed bed reactors with diameters below 1 cm, millipacked beds hereafter, are often used to test catalysts. The prospect of using these reactors for catalytic kinetic measurements is quite attractive, but it requires a better knowledge of the flow characteristics of these reactors. This study focuses on the main hydrodynamic features of millipacked bed reactors in single phase gas flow. The effects of the bed length, gas velocity, reactor/particle diameter ratio ( δ ) and the use of fine inert powder as porosity filler are investigated via residence time distribution measurements and reactive tests. When using spherical particles, for values of reactor/particle diameter ratios between 1 < δ < 3, the behavior of the Peclet number, Pe, is not monotonous. Lower values of the Pe number for specific values of δ corresponding to large void spaces between the particles and/or between the particles and the walls, have been observed. For values of δ > 3 higher Pe numbers are observed, in particular at high gas velocities, due to the transition to a more uniform packing where the walls are no longer the major constraint. When using cylindrical particles, higher dispersion is observed when the cylinders align on each other along the reactor axis, as compared to when they are randomly arranged in the reactor. A criterion to calculate the maximum conversion that can be achieved neglecting dispersion effects has been proposed, highlighting the situations where it has to be used with caution. The dispersion in these reactors can often be neglected. In case the criterion is not fulfilled, filling the porosity of the beds with powder reduces the dispersion. Using porosity fillers in reactors with internal diameters between 2 and 4 mm showed an improvement of the conversions for n -heptane reforming and methylcyclohexane dehydrogenation, which is attributed to external mass transfer improvement. Fine and spherical powders fill better the porosity and yield lower dispersion and higher mass transfer.